Evolution of the United States public land surveys - Harvey, James Madison (My University, 1898)
Introduction: The present system of surveying the public lands of the United States was inaugurated by a committee appointed by the Continental Congress, and consisting of the following delegates: Thomas Jefferson, chairman, Virginia. Hugh Williamson, North Carolina. David Howell, Rhode Island. Elbridge Gerry, Massachusetts. Jacob Read, South Carolina. On the 7th of May, 1784, this committee reported “An ordinance for ascertaining the mode of locating and disposing of lands in the western territory, and for other purposes herein mentioned.” This ordinance required the public lands to be divided into “hundreds” of ten geographical miles square, the “hundreds” to be subdivided into lots of one mile square each, to be numbered from 1 to 100, commencing in the northwestern corner, and continuing from west to east and from east to west consecutively. This was considered, debated, and amended, and reported to Congress April 26, 1785. As reported, this required surveyors “to divide the said territory into townships 7 miles square, by running lines due north and south, and others crossing these at right angles.
Citation: Harvey, James Madison. Evolution of the United States public land surveys. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Public Lands; Surveying; Continental Congress; Western Territory; Theses; Manuscripts (documents)